ANALISIS PENDAPATAN OPERASIONAL BANK BUMN INDONESIA PERIODE 2016-2021 - Muhammad Fauzan Aziz (2022)
Competition is inevitable for businesses. The emergence of competition is not only felt by financial institutions but also by banking institutions. Competition between banks to retain customers and acquire new customers is now getting tougher. This is evidenced by the number of new banks being born today. Banks generally derive two kinds of income from their operational activities, namely spread based income and fee based income. Spread based income is income generated from the difference between interest on deposits and interest on loans/credits or it can be said as income from interest results. Meanwhile, fee-based income is the bank's income obtained through banking services or it can be said as income from non-interest income. In the era of increasingly fierce business competition, Indonesian banks continue to strive to improve their quality in lending/credit and services in providing banking services as a driver of the country's economy. The quality of these banks can be seen in the income received by each bank. An increase in income results in each period of the year indicates that the bank's performance is getting better, and vice versa if it decreases, it indicates that the bank's performance is deteriorating.